Pengaruh Customer Relationship Management, Kualitas Produk serta Kepercayaan Konsumen Terhadap Loyalitas Pelanggan ( Studi Kasus PT Injaya Cipta Mandiri Makmur ) - Tatang Iman Sadewo (Journal Of Communication Education, 2018)
ABSTRACT- The Effect of Customer RelationshipManagement, Product Quality and Consumer Truston Customer Loyalty. PT. Injaya Cipta MandiriMakmur is a plastic sack company in Banten. In itsmanagement for 4 years in the third year experienceda significant turnover decrease. This is caused byvarious factors, including Customer RelationshipManagement, Product Quality and Consumer Trust.To analyze the problem, multiple regression analysiswith 100 samples was selected based on purposivesampling with Customer Relationship Managementvariables, Product Quality and Consumer Trust andCustomer Loyalty.In conclusion, this study provedthat 3 variables that have a positive effect are thevariables of Customer Relationship Management,Product Quality and Consumer Confidencesignificantly. Suggestions for variable ProductQuality so that companies always provide qualityproducts and improve good Consumer Trust.Keywords : Customer Relationship Management,Product Quality and Consumer Trust onCustomer Loyalty.